Konflik Batin pada Novel Kemelut Rondasih dan Dua Anaknya Karya Minanto - Hakim, Frizy Azizul; Juidah, Imas; Logita, Embang (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2025)
This study aims to reveal the inner conflict of the main character in the novel Kemelut Rondasih dan Dua Anaknya by Minanto through a literary psychology approach, especially Abraham Maslow's humanistic theory. Rondasih is described as a woman who grew up in an incomplete family environment and faced psychological, social, and economic pressures. This study uses a qualitative descriptive method with listening and note-taking techniques, as well as content analysis to trace quotations that reflect the character's inner conflict. The results of the analysis show that the conflict is closely related to the unfulfilled physiological needs, sense of security, love and belonging, and self-esteem. Failure to meet these needs hinders Rondasih's psychological balance. This study concludes that Maslow's theory is effective in understanding the inner conflict of literary characters. Practically, these findings are useful in learning literature and can be applied in bibliotherapy to develop empathy and self-reflection in readers.